2019
DOI: 10.1108/ijm-09-2018-0300
|View full text |Cite
|
Sign up to set email alerts
|

Do stereotypes about older workers change? A panel study on changing attitudes of managers

Abstract: Purpose The purpose of this paper is to see whether attitudes toward older workers by managers change over time and what might explain development over time. Design/methodology/approach A unique panel study of Dutch managers is used to track the development of their attitudes toward older workers over time (2010–2013) by focusing on a set of qualities of older workers aged 50 and older. A conditional change model is used to explain the variation in changes by focusing on characteristics of the manager (age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 54 publications
3
22
0
1
Order By: Relevance
“…When comparing ISCO group 1–4 (mainly seated work) with ISCO group 5–9 (mainly physical work), employees from ISCO group 5–9 were significantly less likely to report their managers to have four out of the five positive attitudes, the exception being, “Older workers are easy to cooperate with”. These findings support previous studies indicating that the attitudes towards older workers varies across occupational groups [ 19 , 21 , 22 , 23 , 24 , 27 ] and that managers in white-collar jobs may have less negative attitudes towards older workers [ 21 , 22 ]. Surprisingly, the results showed that respondents from ISCO groups 5–9 were also significantly less likely to believe their managers to have three of the five directly negative perceptions of older workers.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…When comparing ISCO group 1–4 (mainly seated work) with ISCO group 5–9 (mainly physical work), employees from ISCO group 5–9 were significantly less likely to report their managers to have four out of the five positive attitudes, the exception being, “Older workers are easy to cooperate with”. These findings support previous studies indicating that the attitudes towards older workers varies across occupational groups [ 19 , 21 , 22 , 23 , 24 , 27 ] and that managers in white-collar jobs may have less negative attitudes towards older workers [ 21 , 22 ]. Surprisingly, the results showed that respondents from ISCO groups 5–9 were also significantly less likely to believe their managers to have three of the five directly negative perceptions of older workers.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, findings indicate that older managers [ 13 , 21 , 22 , 23 ] and managers that are in more frequent contact with older workers [ 13 ] hold more positive attitudes towards older workers. A recent study found that concrete experiences with older workers influenced the managers′ perceptions of older workers [ 24 ], indicating that it is not enough merely to have frequent contact with older workers to develop more positive attitudes towards them; the concrete experiences have to be positive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained in the article cited above also confirms the conclusions of other authors [50] who conducting research among Dutch managers during 2010-2013, regarding the attitudes and conditioning towards older employees. Although research has shown lasting stability of attitudes, their slight variation was observed among others depending on the age of managers, their education, gender, seniority and experience in relations with older employees.…”
Section: Attitudes Towards 65+ Knowledge Workerssupporting
confidence: 86%
“…Riach-Rich [2010] szerint az első ilyen jellegű kordiszkriminációt bemutató cikk Jowell-Prescott-Clarke [1970] volt. mára ez a módszer általánossá vált, és mint ahogy Dalen-Henkens [2019] megmutatta, arra is kiválóan alkalmas, hogy feltárják a munkáltatói elképzelésekben a körülmények hatására bekövetkezett változásokat. a kutatás leírása 1 Kísérletünkben két-két női állásjelentkezőt "alkottunk meg" önéletrajzzal, fényképpel és a valóságban is létező telefonnal, e-mail-címmel együtt.…”
unclassified